A case study of campus-based initiatives to disaster awareness program: the road to resilience - How, Vivien; Peter, Pamela Jude; Martinus, Kenny Brian; Mohd Dzahir, Norjihan; Ali, Ain Izzati; Ahmad Dzahiruddin, Nur Deena Adzlynn; Zainal Aripin, Mohd Fikri (OALib Journal, 2015)
Introduction: The Hyogo Framework for Action (HFA) to build the resilience of nations and communities to disasters has been proposed since year 2005. Even though educational based disaster risk reduction programs have been conducted by the institutional agencies for years, communities are still weak in response to disaster preparedness. The current efforts need to be revised to understand the possible dilemma of moving the community from fragility to resilience. Objective: To examine the community perception of the disaster preparedness and response, and their readiness to become the resilient community. Methodology: This is a case-study conducted among 40 participants at the age of 18 - 29 years from a local private college. A campus-based disaster awareness seminar was initiated into a strategized learning framework to facilitate knowledge transfer and foster awareness built among the participants. The program framework consists of three sections: 1) to expose the participant with information on visual-aid and interactive discussion; 2) to involve the public involvement in hands-on practice bandages and dressings; 3) to evaluate the public’s readiness and acceptance towards a resilience nation based on a survey questionnaire. Result: 75% of the educated respondents claimed that they did not consider themselves as the resilient group of the disaster, and 55% referred to the non-validated news from internet/ social media as the source to gather information. Nevertheless, most of the participants have expressed common expectations, such that 1) to share experiences and knowledge about disaster risk reduction planning and response; 2) to learn how to empower the local community during disasters. Conclusion: It is truth that urban and educated groups are fragile in response to the disaster. Nonetheless, knowledge transfer is one of the most feasible approaches to building a resilient community and fostering a nation who is able to withstand and recover from any upcoming disaster with sustainable development.